Struktur Modal Dan Profitabilitas Pada Nilai Perusahaan Bidang Jasa Sektor Perbankan - Makhmudi, Mario Aditya; Zulkifli, Makhmud (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to investigate the influence of capital structure on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2021. Additionally, it seeks to examine the impact of profitability on firm value in these banking companies for the period 2018-2021. The research utilizes an explanatory research design, and data is sourced from the IDX website covering the years 2018-2021. Data analysis involves ratio analysis and multiple linear regression analysis using SPSS 25. The findings reveal that capital structure, measured by debt to asset ratio and debt to equity ratio, shows a positive and significant influence on firm value (PBV), with the latter being the more impactful. Profitability, measured by return on assets and return on equity, indicates that only return on equity has a positive and significant effect on firm value (PBV). The simultaneous results demonstrate that both capital structure and profitability have a positive and significant impact on firm value (PBV).